Expanding the Intellectual Property Knowledge Base at University Libraries: Collaborating with Patent and Trademark Resource Centers. - Martin Wallace; Suzanne Reinman (Issues in Science and Technology Librarianship, 2018)
Patent and Trademark Resource Centers are located in libraries throughout the U.S., with 43 being in academic libraries. With the importance of incorporating a knowledge of intellectual property (IP) and patent research in university curricula nationwide, this study developed and evaluated a partnership program to increase the understanding of IP and patent searching methods at universities that do not headquarter a PTRC. This article describes the methods for establishing those partnerships, summarizes their results, and offers a list of best practices and lessons learned for establishing future partnerships. [ABSTRACT FROM AUTHOR]